A reusable, reagent-less free chlorine sensor using gold thin film electrode. Issue 8 (3rd March 2021) - Alam, Arif Ul; Clyne, Dennis; Lush, Will; Deen, M. Jamal
Abstract : Free chlorine is widely used as a disinfectant in the water industry. Abstract : Free chlorine is widely used as a disinfectant in the water industry. Accurate monitoring of the residual free chlorine concentration in water cycles is critical to maintain public health safety. Here, we report on a thin gold film-based reusable and reagent-less free chlorine sensor. A gold thin film of 300 nm thickness was deposited on a polyimide tape, which was placed on a glass substrate and a simple Styrofoam adhesive tape was used to cover the film and expose 0.36 cm2 circular area as the sensing surface. The sensor showed a high sensitivity of 0.327 μA ppm −1, with a linear range of 0 to 6 ppm, and an accuracy of <0.1 ppm with high selectivity in the presence of commonly interfering ions. The sensor response time was 50 s with a negligible hysteresis of 0.06 ppm. The sensor showed very little change in output current in the pH range between 5.2 to 8.4, and temperature range of 20 to 30 °C. Therefore, the sensor operation is reagent-less, does not need frequent calibration, and showed consistent sensing performance with real water samples. The simple fabrication, ease-of-use and reliable sensing performance of the proposed sensor shows feasibility for mass-production and application in remote and resource-limited areas.